Impact of Failure in Exam on the Performance of Student: Understanding the Consequences of Exam Failure on Student Performance (Journal of Advances and Scholarly Researches in Allied Education, 2014)
The level of competition is increasing in the world. In this running life, everyone wants to beat others to reach at next level. In every field of life, the pressure to perform well can be seen easily. Everyone is so busy to compete with others. Education field is no more unaffected of this fact. In fact, the level of competition is increasing at a rapid pace in this field. The level of percentage of marks is increasing year by year. Companies also recruit only those students having higher percentage of marks. Due to all these factors; the family members, relatives or even teachers put a high pressure on students to perform well during the exams. Their expectations are too high that some students can’t fulfill that and go into depression. The current paper highlights the impact of failure in exam on the performance of student.